2021
DOI: 10.3390/cancers13205189
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus—Associated Malignancies and Immune Escape: The Role of the Tumor Microenvironment and Tumor Cell Evasion Strategies

Abstract: The detailed mechanisms of Epstein–Barr virus (EBV) infection in the initiation and progression of EBV-associated malignancies are not yet completely understood. During the last years, new insights into the mechanisms of malignant transformation of EBV-infected cells including somatic mutations and epigenetic modifications, their impact on the microenvironment and resulting unique immune signatures related to immune system functional status and immune escape strategies have been reported. In this context, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 308 publications
(401 reference statements)
1
51
0
Order By: Relevance
“…The data set of Jima et al 34 utilized HG-U133A gene chips (Affymetrix) for the analysis of flow cytometry sorted CD19-positive B cells of healthy human donors, while the study of Kim and co-authors 35 applied the same gene chips and investigated EBV-positive BL. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…The data set of Jima et al 34 utilized HG-U133A gene chips (Affymetrix) for the analysis of flow cytometry sorted CD19-positive B cells of healthy human donors, while the study of Kim and co-authors 35 applied the same gene chips and investigated EBV-positive BL. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Epstein Barr Virus might be useful in the development of vaccines and immune cell therapy for EBV-Associated diseases, especially for several immune-related diseases 44 . The prognosis of Epstein–Barr virus infection in UC was less paid attention to 45 . In this study, the KEGG pathways results indicated that more studies of the Epstein–Barr virus infection pathway in UC could be conducted 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is a double stranded DNA virus in the herpesvirus family [128]. It was discovered by Dr. Epstein and his assistant, Ms. Barr, during a global investigation into the cause of Burkitt's lymphoma in the 1960s [129].…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinogenesismentioning
confidence: 99%
“…[140]. EBV-specific products LMP1 [141] and LMP2 [142] also alter the cell cycle and aid in immune evasion [128]. Additional risk factors for NPC include regular consumption of salted fish and Southeast Asian heritage.…”
Section: Figure 3 Growth and Immune Evasion Of Ebv-mediated Npc Typic...mentioning
confidence: 99%